Developing learning activity based on the learning cycle approach to promote students' understanding of square root - Shimu Shahana Sheikh (2018)
Most countries are concerned about mathematics education for students do not perform well in this subject, especially on the topic of square root, owing to the lack of motivation in traditional learning activities. In such learning activities, teachers describe the calculation of square roots of numbers using the long division procedure step-by-step, while students try to follow that procedure without understanding the reason behind it, which results in poor performance. Therefore, to promote secondary students' understanding on square roots of numbers, this study developed square root learning activities based on the learning cycle approach. The students started by exploring the relationship between that number and its square, and were asked to predict and verify the relationship using the concept of algebra. Next, the concept of the square root of a number was explained, and the comparison between using algebra and using the long division procedure for calculating the square root of a number was discussed. Finally, the students applied algebra, along with the long division procedure, to solve their own tasks. Thirty-eight seventh grade secondary-school students were recruited to participate in this study. The research design was quasi-experimental design. By analyzing the data from conceptual preand post-tests, the students who participated in the developed learning unit could improve their learning achievement on the topic. Moreover, the results from a questionnaire showed that they were satisfied with the developed learning activities, and responded that the developed learning unit helped them understand the procedure of finding the square root of numbers. © Common Ground, Shimu Shahana Sheikh, Patcharin Panjaburee, Parames Laosinchai, Niwat Srisawasdi.